Video data quality improvement methods and tools development for mobile vision systems - Dergachov, Kostiantyn; Krasnov, Leonid; Cheliadin, Oleksandr; Kazatinskij, Roman (Національний технічний університет "Харківський політехнічний інститут", 2020)
The paper formulates a comprehensive criterion for improving the quality of the Raspberry Pi microcomputer video input and preprocessing video data. Based on the accepted quality indicators (video input speed, resolution, and stability indicators of average brightness of the current frames of the received video stream), video input and preprocessing algorithms that satisfy the specified requirem ents are synthesized. This allows to find the optimal method forprocessing video data and to overcome the contradiction of reducing the input speed due to the need of increasing the resolution of video frames for each project. The created universal program for input and preliminary processing of these data allowed to obtain quantitative estimates of the effectiveness of the developed algorithms and formulate recommendations for their further use. All this allows you to significantly increase the efficiency of using Raspberry Pi microcomputers in modern mobile vision systems.

В роботі сформульовано комплексний критерій підвищення якості введення в мікрокомп'ютер Raspberry Pi і попередньої обробки відеоданих. На підставі прийнятих показників якості (швидкості введення відеоданих, роздільної здатності та показників стабільності середньої яскравості поточних кадрів прийнятого відеопотоку) синтезовані алгоритми введення і попередньої обробки відеоданих, що задовольняють заданим вимогам. Це дозволяє для кожного проекту знайти оптимальний метод обробки відеоданих і подолати протиріччя зменшення швидкості введення через необхідність збільшення роздільної здатності відеокадрів. Створена універсальна програма введення і попередньої обробки цих даних дозволила отримати кількісні оцінки ефективності розроблених алгоритмів і сформулювати рекомендації щодо їх подальшого використання. Все це дозволяє істотно підвищити ефективність використання мікрокомп'ютерів Raspberry Pi в сучасних мобільних системах технічного зору.
Розробка нових методів і засобів підвищення якості відеоданих в мобільних системах технічного зору
Keywords: Raspberry Pi microcomputer; algorithms and program codes for input and preprocessing of video data; OpenCV library functions; мікрокомп'ютер Raspberry Pi; алгоритми і програмні коди введення і попередньої обробки відеоданих; функції бібліотеки OpenCV